Faktor-Faktor yang Berkaitan dengan Pengetahuan Perawatan Kaki di Kalangan Pasien Diabetes Melitus - Ismail Ismail; Hamzah Tasa; Syamsir Syamsir (Celebes Health Journal, 2026)
Background: Diabetes mellitus is a chronic disease with a steadily increasing prevalence and is frequently accompanied by foot complications that substantially impair patients’ quality of life. Diabetic foot complications, including foot ulcers, can be prevented through appropriate foot care practices. Foot care knowledge is a critical component in shaping self-care behaviors; however, patients knowledge levels remain variable and are influenced by sociodemographic factors, clinical characteristics, and exposure to health information. Objective: This study aimed to analyze factors associated with foot care knowledge among patients with diabetes mellitus. Methods: This analytic observational study employed a cross-sectional design. The study was conducted at Sudiang Raya Primary Health Care Center from October to December 2025. A total of 80 patients with diabetes mellitus were recruited using a total sampling technique. Data were collected from the primary health care database and structured questionnaires assessing participants’ characteristics and foot care knowledge. Data analysis included descriptive analysis, bivariate analysis using Chi-square or Fisher’s exact tests with calculation of odds ratios and 95 % confidence intervals, and Receiver Operating Characteristic (ROC) analysis to evaluate the discriminative ability of the model using the Area Under the Curve (AUC). Results: The results demonstrated that age, educational level, employment status, duration of diabetes mellitus, and exposure to health information were significantly associated with foot care knowledge. Exposure to information emerged as the most dominant factor and significantly increased the likelihood of patients having good foot care knowledge. Conclusion: Foot care knowledge among patients with diabetes mellitus is influenced by a combination of sociodemographic factors, clinical characteristics, and exposure to health information. These findings highlight the importance of structured, continuous, and contextually appropriate foot care education as an integral component of diabetes nursing care to prevent foot-related complications.